Analisa Performansi Algoritma Routing Dtn Maxprop Dan Spray And Wait Pada Vehicular Ad Hoc Network (vanet) - Sofia Nafila Putri; Leanna Vidya Yovita; Doan Perdana (eProceedings of Engineering, 2016)
Small number of vehicle and high mobility cause some problem in VANET. Since there is no complete end-to-end path cause conventional VANET routing protocol can’t handle an intermittent connectivity and large delay properly. In this research, I implement the DTN routing protocol Maxprop and Spray and Wait to solves the problem in VANET. The performance of Maxprop and Spray and Wait is evaluated by observing the performance parameters of both routing protocol under varying node speed and node volume. Simulation result shows that the increment of node speed reduces the overhead of both routing protocol for about 10.8% for Spray and Wait, and 5.9% for Maxprop. It is also increases the delivery probability of both oruitng protocol about 9.37% for Spray and Wait . The increment of number of node gives the biggest impact and raises the overhead ratio of both routing protocol. The overhead ratio of Maxprop rise for about 74.7% and Spray and Wait for about 88%.